2013
DOI: 10.21009/jrskt.031.04
|View full text |Cite
|
Sign up to set email alerts
|

http://journal.unj.ac.id/unj/index.php/jrskt/article/view/19

Abstract: AbstrakDalam upaya menghasilkan warna kain sutera yang tahan luntur terhadap gosokan serta kuat dan tahan terhadap bakteri, dilakukan suatu penelitian untuk membuat kain sutera berwarna yang tahan gosok dan tahan luntur. Kain sutera yang tahan warna dan tidak luntur, dihasilkan melalui pelapisan permukaan kain dengan menggunakan nanopartikel kitosan. Nanopartikel kitosan yang dibuat melalui reaksi ikatan silang gugus amina (-NH 2 + ) pada kitosan dengan gugus phosphat ( -PO 4 ) -3 dari sodium tripolophosphat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…For this reason, this impact can be in the form of direct (direct) and indirect (nurturant) impacts. Implementation of learning with the TAGUNTA learning model has a positive impact on student behavior, both directly and indirectly (Hendrik et al, 2022). Other study found that the direct impact is obtained from student learning outcomes (Sani & Yuliasma, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…For this reason, this impact can be in the form of direct (direct) and indirect (nurturant) impacts. Implementation of learning with the TAGUNTA learning model has a positive impact on student behavior, both directly and indirectly (Hendrik et al, 2022). Other study found that the direct impact is obtained from student learning outcomes (Sani & Yuliasma, 2022).…”
Section: Discussionmentioning
confidence: 91%